TINDAK PIDANA KORUPSI PADA PEKERJAAN SWAKELOLA - Hairwansyah Arif; Ali Rizky; Abdul Jabar Rahim (Journal Publicuho, 2024)
The purpose of this writing is to determine criminal acts of corruption in self-managed work, especially misuse of funds and manipulation of data, requiring a holistic approach. This research uses normative legal research methods. Normative research is research carried out by examining library materials. The data used in this research is secondary data which includes primary legal materials, namely statutory regulations. Then this research also uses secondary legal materials, namely legal materials that provide an explanation of primary legal materials. The research results show that in the face of criminal acts of corruption using data manipulation, steps that strengthen supervision and control over the reporting and project documentation process are very important. Providing an integrated and transparent information system will help minimize the risk of data manipulation by providing easier and more transparent access to project information for related parties. Apart from that, increasing the capacity and integrity of auditors and law enforcers in detecting and taking action against data manipulation practices will be key in tackling criminal acts of corruption.